Elbow, wrist kinematics and shock transmission of backhand stroke in wheelchair tennis players - Ju, Y.-Y.; Chu, W.-T.; Shieh, W.-Y.; Cheng, H.-Y. K. (Sports Biomechanics, 2021)
The aim was to compare the differences in kinematics of elbow and wrist and shock transmission of the upper extremity in wheelchair tennis players and able-bodied players (in standing and sitting position) during backhand strokes. Fifteen wheelchair tennis and 15 able-bodied tennis players enrolled. Electromagnetic system and trial-axial accelerometers were used to measure the difference in the kinematic parameters of the upper extremity and the impact vibration transferred across the wrist joint. The results indicated that wheelchair players demonstrated unique elbow and wrist kinematics, especially shorter total swing time, greater elbow flexion at preparation, lower wrist extension acceleration before impact, and smaller racket vibration at impact. Comparing to able-bodied players in standing, wheelchair players and players in sitting demonstrated significantly greater elbow joint flexion/extension angle, angular velocity, angular acceleration during extension, and wrist joint flexion angle. Wheelchair players also differ significantly with the players in sitting regarding elbow joint angular velocity and acceleration, and wrist joint flexion velocity. These adaptations and adjustments can be attributed to the missing lower extremity function and deficient trunk kinetic chain. The differences between wheelchair tennis players and able-bodied players in sitting could represent the progress as the wheelchair players moving from novices to experts.